Program Budgeting in Malaysia : Implementing the Outcomes-Based Approach in Malaysia - World Bank (Washington, DC, 2013)
This report summarizes the results of a two-day fact finding mission and a two day workshop conducted by the Economic Planning Unit of the Prime Minister s Department in collaboration with the World Bank's Public Sector Performance Global Expert Team (PSP-GET) held at the beginning of March in 2010 in Putrajaya, Malaysia. Prior to the workshop, the team held meetings with officials from the EPU, the Ministry of Finance, the Ministry of Transport, and the Ministry of Health to better understand the coordination and implementation challenges facing these entities with regard to adopting an outcomes-based approach (for a summary of the issues discussed please see Appendix). This report covers the critical areas to consider when implementing an outcomes-based approach. These include the organization and allocation of responsibilities, the design of the implementation process, the function of a Monitoring and Evaluation (M and E) system, change management, and the risks associated with such a transition. Each section is then structured in the following way: Issues identified during the discussions; relevant experience from the two main case study countries (Korea and Australia); and overall findings of the PSP-GET team.